Surfactant Proteins A/D–CD14 on Alveolar Macrophages Is a Common Pathway Associated With Phagocytosis of Nanomaterials and Cytokine Production - Wang, Qiqi; Wang, Qiong; Zhao, Ziyue; Fan, Jingbo; Qin, Linghan; Alexander, David B.; Tsuda, Hiroyuki; Zhao, Dahai; Xu, Jiegou (Frontiers in Immunology, 2021)
Alveolar macrophages are responsible for clearance of airborne dust and pathogens. How they recognize and phagocytose a variety of engineered nanomaterials (ENMs) with different properties is an important issue for safety assessment of ENMs. Surfactant-associated proteins, specifically existing in pulmonary surfactant, are important opsonins for phagocytosis of airborne microorganisms. The purposes of the current study are to understand whether opsonization of ENMs by surfactant-associated proteins promotes phagocytosis of ENMs and cytokine production, and to determine whether a common pathway for phagocytosis of ENMs with different properties exists. For these purposes, four ENMs, MWCNT-7, TiO2, SiO2, and fullerene C60, with different shapes, sizes, chemical compositions, and surface reactivities, were chosen for this study. Short-term pulmonary exposure to MWCNT-7, TiO2, SiO2, and C60 induced inflammation in the rat lung, and most of the administered ENMs were phagocytosed by alveolar macrophages. The ENMs were phagocytosed by isolated primary alveolar macrophages (PAMs) in vitro, and phagocytosis was enhanced by rat bronchioalveolar lavage fluid (BALF), suggesting that proteins in the BALF were associated with phagocytosis. Analysis of proteins bound to the 4 ENMs by LC/MS indicated that surfactant-associated proteins A and D (SP-A, SP-D) were common binding proteins for all the 4 ENMs. Both BALF and SP-A, but not SP-D, enhanced TNF- production by MWCNT-7 treated PAMs; BALF, SP-A, and SP-D increased IL- production in TiO2 and SiO2 treated PAMs; and BALF, SP-A, and SP-D enhanced IL-6 production in C60 treated PAMs. Knockdown of CD14, a receptor for SP-A/D, significantly reduced phagocytosis of ENMs and SP-A enhanced cytokine production by PAMs. These results indicate that SP-A/D can opsonize all the test ENMs and enhance phagocytosis of the ENMs by alveolar macrophages through CD14, suggesting that SP-A/D-CD14 is a common pathway mediating phagocytosis of ENMs. Cytokine production induced by ENMs, however, is dependent on the type of ENM that is phagocytosed. Our results demonstrate a dual role for surfactant proteins as opsonins for both microbes and for inhaled dusts and fibers, including ENMs, allowing macrophages to recognize and remove the vast majority of these particles, thereby, greatly lessening their toxicity in the lung.